Pengaruh Hedonic Value, Service Quality Dan Price Label Serta Experience Terhadap Purchase Decision Melalui Word of Mouth Dan Purchase Intention Pada Pengunjung Indomaret Di Kota Samarinda - Zuhriah Zuhriah; Hendrik Batoteng; Nur Fitri Amalia Gading (Politeknik Negeri Samarinda, 2020)
This study discusses retail, consumer behavior in shopping and explanations of variable purchase decisions on Indomaret visitors in Samarinda city along with variables that affect hedonic value variables, service quality, price tags, and experience, word of mouth and purchase intention. Discusses some of the theories used as a reference to assist this research, as well as theories relevant to the objects and variables studied, namely marketing theory, service marketing theory, retail marketing theory, understanding of marketing mix and understanding consumer behavior. Then explain the definition of each variable used in this study. The analysis technique used in this study is to use SEM (Structural Equation Modeling) with the help of AMOS (Analysis Moment of Structure) software. The characteristics of the respondents in this study, the test results using AMOS software, obtained a fit and significant relationship between each variable, there is also a direct effect, an indirect effect, and a total effect.